The Use of “Kahoot” (Online Quiz Application) in Teaching Grammar for Second Year Students at SMA Pembangunan Laboratorium UNP - Rahaka Panji Prawira; Mukhaiyar Mukhaiyar (Universitas Negeri Padang, 2020)
This research is motivated by the lack of mastery of Grammar in students. This is because the practice in the learning process is still not varied, one example of an exercise that can be used is Kahoot. This study aims to determine the effectiveness of the use of Kahoot on the teaching of Grammar students in the second year of the SMA Pembangunan Laboratorium UNP. This research uses a quantitative with quasi-experimental methods “pre-test and post-test control group design”. The population in this study were second year students of SMA Pembangunan Laboratorium UNP who were registered in the June-December period of the 2019/2020 school year. The research sample was 20 students of class XI IBB as the experimental class and 22 students of class XI MIPA 1 as the control class. The data of this study are the scores of the final test results of Grammar teaching without and using Kahoot second year students of SMA Pembangunan Laboratorium UNP. The test scores were compared using the t-test formula to determine the effectiveness of using Kahoot in Grammar teaching. Based on the results of the t-test, it was concluded that learning using Kahoot was effective in the teaching of Grammar in the second year students of SMA Pembangunan Laboratorium UNP because tcount> ttable (4.75> 1.68) at a significant level of 0.05. So, it was concluded that the teaching of Grammar in the second year students of SMA Pembangunan Laboratorium UNP by using Kahoot was better than without using Kahoot.